STUDIES ON ANTAGONISTIC ACTIVITY AND PROBIOTIC PROPERTIES OF ENTEROCOCCUS FAECIUM AND LACTOCOCCUS LACTIS - SIVARAJ ANBARASU; MANIKKAM RADHAKRISHNAN; ARUMUGAM SURESH; JERRINE JOSEPH; VANAJA KUMAR (International Journal of Pharma and Bio Sciences, 2014)
The present study compared the antagonistic activity and probiotic properties of two Lactic Acid Bacteria (LAB) such as Enterococcus faecium NCIM 2605 and Lactococcus lactis NCIM 2606. Bacteriocin from both the cultures was produced using MRS broth by shake flask fermentation. In well diffusion method, the cell free supernatant (CFS) of E. faecium showed activity against both gram positive and gram negative organisms especially methicillin resistant S, aureus (MRSA). Maximum inhibition was observed against B. subtilis and V. parahaemolyticus. The CFS of L. lactis showed activity against only gram-positive organisms, but not against MRSA. Both the isolates produced bacteriocin at maximum quantity during the exponential phase at pH 6 and pH 7 when incubated at 370C. The arbitrary unit for E. faecium and L. lactis found to be 3,200 AU/ml and 800AU/ml, respectively. The antimicrobial substances was retaining the activity after treated upto 1210 C for 15 minutes, stable at pH values between 2.0 and 5.0 and 2.0 and 9.0 for E. faecium and L. lactis respectively. Both the substances were found to be sensitive to proteinase K. The tested two LAB survived for 3 hours in the presence of 0.3% w/v bile and pH 3 at 370 C. The strain E. faecium having a broad spectrum of activity, possess probiotic ability than the L. lactis and can be developed as probiotic diary fermented products.